The genetic architecture of membranous nephropathy and its potential to improve non-invasive diagnosis - Xie, Jingyuan; Liu, Lili; Mladkova, Nikol; Li, Yifu; Ren, Hong; Wang, Weiming; Cui, Zhao; Lin, Li; Hu, Xiaofan; Yu, Xialian; Xu, Jing; Liu, Gang; et al. (Nature Communications, 2020)
Membranous Nephropathy (MN) is a rare autoimmune cause of kidney failure. Here we report a genome-wide association study (GWAS) for primary MN in 3,782 cases and 9,038 controls of East Asian and European ancestries. We discover two previously unreported loci, NFKB1 (﻿rs230540, OR = 1.25, P = 3.4 × 10−12) and IRF4 (﻿rs9405192, OR = 1.29, P = ﻿1.4 × 10−14), fine-map the PLA2R1 locus (﻿rs17831251, OR = 2.25, P = 4.7 × 10−103) and report ancestry-specific effects of three classical HLA alleles: DRB1*1501 in East Asians (OR = 3.81, P = 2.0 × 10−49), DQA1*0501 in Europeans (OR = 2.88, P = 5.7 × 10−93), and DRB1*0301 in both ethnicities (OR = 3.50, P = 9.2 × 10−23 and OR = 3.39, P = 5.2 × 10−82, respectively). GWAS loci explain 32% of disease risk in East Asians and 25% in Europeans, and correctly re-classify 20–37% of the cases in validation cohorts that are antibody-negative by the serum anti-PLA2R ELISA diagnostic test. Our findings highlight an unusual genetic architecture of MN, with four loci and their interactions accounting for nearly one-third of the disease risk.
CRIS-Team Scopus Importer:2020-04-07